Concerning the observance of bilingualism in document management in Kazakhstan in 1985–1991 years - Baigozhina, G.M. (Академик Е.А. Бөкетов атындағы Қарағанды университеті, 2024)
The article studies the problems of observance of bilingualism in document management in 1985–1991. At the beginning of perestroika, the intensification of the democratization processes of society led to a new up-surge of many unresolved problems including social, ethnic, etc. during the Soviet period. One of such acute problems for Kazakhs was the issue of the reduction of the Kazakh language in all spheres of public life. Dur-ing the period under review, the top party leadership recognized the problems in language policy. G.V. Kolbin criticized the party organization of the republic for ignoring the problems of the Kazakh lan-guage and the necessity of equal use of the Kazakh and Russian languages in document management at the Plenum of the Central Committee of the Communist Party of Kazakhstan in January 1987. The article is based on the archival materials of the Archive of the President of the Republic of Kazakhstan. The author studies the resolutions “On improving the study of the Kazakh language in the Republic” and “On improving the study of the Russian language in the Republic”, which raised the issues of development and dissemination of Kazakh-Russian bilingualism in the Republic under consideration. The author concluded that the organiza-tion of work on the introduction of office work in the Kazakh language did not meet the demands of the Ka-zakh-speaking population. On the example of areas with a predominantly Kazakh population, the author shows that office work was conducted in Russian. The dominance of the Russian language in the most pres-tigious spheres of social activity often had negative socio-psychological consequences for Kazakhs.
1985-1991 жылдары Қазақстанда іс қағаздарын жүргізуде қостілділік қағидатын сақтау мәселесі туралы
К вопросу о соблюдении принципа двуязычия в делопроизводстве в Казахстане в 1985–1991 гг.
Keywords: Kazakh language; Russian language; bilingualism; document management; Kazakh SSR; national policy; Kazakhs; interethnic relations; language policy; resolutions